Employing DNA metabarcoding to determine the geographical origin of honey. Issue 11 (November 2020) - Khansaritoreh, Elmira; Salmaki, Yasaman; Ramezani, Elias; Akbari Azirani, Tayebeh; Keller, Alexander; Neumann, Katrin; Alizadeh, Kamaleddin; Zarre, Shahin; Beckh, Gudrun; Behling, Hermann
Abstract: Unfavourable climatic conditions force Iranian beekeepers to translocate over large distances in the course of the year. However, irrespective of the main place of production, the honey is always labeled with the name of the beekeepers' hometown, which leads consequently to mislabeled products. The present study investigates the capability of DNA metabarcoding to locate the geographical origin of honey. The molecular markers (ITS2 and rbcL ) allowed identification of 926 plant species in studied samples. A comprehensive review of floristic reference books specified 34 key species that could be used to successfully determine the geographical origin in 91.4% of samples. These key species were usually present in honey with tiny amounts and thus, conventional palynology might not be able to detect them. The present investigation indicates that although ITS2 is able to detect more species than rbcL, utilizing a combination of both markers provides more robust evidence of geographical origin. Abstract : Food science, Food analysis, Food technology, Molecular biology, Honey, Geographical origin, Metabarcoding, ITS2, rbcL